Effect of short-term intensive insulin pump therapy on serum endotrophin levels in patients with newly diagnosed type 2 diabetes - Li, Yuting; Gui, Xiaoting; Weng, Yu; Xun, Lizhang; Yu, Weinan; Xiang, Chunli; Qi, Xing; Wang, Xiaoqing; Bai, Feng (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the effect of short-term intensive insulin (STII) pump therapy on serum endotrophin (ETP) levels in patients with newly diagnosed type 2 diabetes, examine the relationship between serum ETP levels and insulin resistance (IR).Subjects and methodsOur study recruited 40 patients with newly diagnosed type 2 diabetes and 40 healthy controls. First, we compared the serum ETP levels between patients with newly diagnosed type 2 diabetes and controls. Second, 40 patients with newly diagnosed type 2 diabetes underwent two weeks of STII pump therapy.ResultsHigher serum ETP levels were observed in patients with newly diagnosed type 2 diabetes compared to controls. After 2 weeks of STII pump therapy, serum ETP levels significantly attenuated in patients with newly diagnosed type 2 diabetes. Both before and after treatment, serum ETP exhibited a significant positive correlation with homeostasis model 2 assessment of IR (HOMA2-IR). Multiple linear regression analysis revealed that changes in ETP levels (δ-ETP) were independently associated with changes in HOMA2-IR (δ-HOMA2-IR).ConclusionsSerum ETP serves as a risk factor for type 2 diabetes and correlates with insulin resistance index. STII contributed to reducing the heightened inflammatory response in individuals with type 2 diabetes.